The environmental impact of beef and ultra-processed food consumption in Brazil - Gabriela Lopes da Cruz; Maria Laura da Costa Louzada; Jacqueline Tereza da Silva; Josefa Maria Fellegger Garzillo; Fernanda Rauber; Ximena Schmidt Rivera; Christian Reynolds; Renata Bertazzi Levy (Cambridge University Press, 2024)
Abstract Objective: This study evaluated the independent and combined environmental impacts of the consumption of beef and ultra-processed foods in Brazil. Design: Cross-sectional study. Setting: Brazil. Participants: We used food purchases data from a national household budget survey conducted between July 2017 and July 2018, representing all Brazilian households. Food purchases were converted into energy, carbon footprints and water footprints. Multiple linear regression models were used to assess the association between quintiles of beef and ultra-processed foods in total energy purchases and the environmental footprints, controlling for sociodemographic variables. Results: Both beef and ultra-processed foods had a significant linear association with carbon and water footprints (P < 0·01) in crude and adjusted models. In the crude upper quintile of beef purchases, carbon and water footprints were 47·7 % and 30·8 % higher, respectively, compared to the lower quintile. The upper quintile of ultra-processed food purchases showed carbon and water footprints 14·4 % and 22·8 % higher, respectively, than the lower quintile. The greatest reduction in environmental footprints would occur when both beef and ultra-processed food purchases are decreased, resulting in a 21·1 % reduction in carbon footprint and a 20·0 % reduction in water footprint. Conclusions: Although the environmental footprints associated with beef consumption are higher, dietary patterns with lower consumption of beef and ultra-processed foods combined showed the greatest reduction in carbon and water footprints in Brazil. The high consumption of beef and ultra-processed foods is harmful to human health, as well as to the environment; thus, their reduction is beneficial to both.